The Role of Nurses in the Management of Pharmaceutical Supplies on Emergency Trolleys in the Palangka Raya City Region Hospital in 2024 - Yusuf, Baharuddin; Dwitanta, Sucipto; Gultom, Okto Riristina (LPPM Institut Pendidikan Nusantara Global, 2025)
Hospital Pharmaceutical Services require a good pharmaceutical supply management system in order to provide the best service for patients. Pharmaceutical services require adequate pharmaceutical supply support such as drugs, medicinal materials, medical devices, reagents, pharmaceutical radios and medical gases as well as Consumable Medical Materials (BMHP). In addition, the Hospital also implements the Regulation of the Minister of Health of the Republic of Indonesia Number 47 of 2018 concerning Emergency Services for services to patients in emergency conditions. The regulation requires the role of all parties such as pharmacists, medical parties such as doctors and nurses. Nurses have a role in health services for patients in accordance with Law 38 of 2014 concerning nursing. The purpose of this study is to conduct a descriptive assessment related to the role of nurses in the management of pharmaceutical supplies in the emergency trolley of hospitals in the Palangka Raya city area in 2024. This research was carried out by making a questionnaire measuring tool that was in accordance with the data of the research variables. The research questionnaire measuring tool will be distributed to nurses in hospitals in the Palangka Raya city area, and in accordance with the inclusion criteria. All respondents' answers will be grouped and processed. The results of the processing of respondents' answer data will be included in the table of descriptive criteria for percentages that have been made, so that conclusions can be drawn. This study obtained the results of the final average value, namely the knowledge aspect of 23.44 points (73.26%), the aspect of administering drugs from the Emergency Trolley of 17.37 points (91.41%), the aspect of procedures and management of drugs in the Emergency Trolley of 25.13 points (86%.64), the aspect of drug documentation in the Emergency Trolley of 3.48 points (87.03%), the aspect of training on drugs available in the Emergency Trolley of 10.34 points (60.83%) and the aspect of managing expired or damaged drugs of 3.16 points (79.11%).The results of this study found that nurses have a role in the management of pharmaceutical supplies on the Emergency Trolley in good criteria with a scale of 78.98%..